JUDGMENT KANTOR URUSAN AGAMA TERHADAP NIKAH USIA MUDA PERSPEKTIF MAQASID SYARI’AH (STUDI KASUS DI KUA KECAMATAN TELUK SEGARA KOTA BENGKULU) - Basil, Sahmul (UIN Fatmawati Sukarno Bengkulu, 2017)
This study raises the issue of judgment KUA officials Segara bay towards young marriage and Maqasid Syariah perspective to judgment KUA officials against young marriage. The purpose of this research is to know. This type of research that is used in preparing this thesis is qualitative data collection techniques of observation, interviews and documentation, obtained through informant interviews at KUA officials and local community leaders. After the data obtained qualitatively analyzed by means of: data reduction (data reduction), presentation of data (data display), and draw conclusions (verification). The results showed that the Gulf KUA officials Segara judgment against young marriage that essentially passive KUA not pick up the ball means KUA only receives and selects the terms proposed by the prospective bridegroom and bride age if found lacking as has been required by the Act No. 1 In 1974, the Syariah perspective Maqasid Overview judgment KUA officials against young age of marriage is correct because Islam maintain the benefit of the family in particular and society in general. This is in accordance with the rules of fiqh “Maslahah Muarsalah” ie assuming that this law is just a tool that the end goal is to create a benefit for mankind. Given madaratnya arising from a young age marriage was a very big influence on domestic and social life, the government reserves the right to make the minimum marriage age limit requirement as stipulated in Law No. marriage 1 of 1974 Article 7 paragraph (1) and KHI Article 15 paragraph (1).